WEB-BASED INFORMATION SYSTEM DESIGN OF INVENTORY AND COVID-19 VACCINE DISTRIBUTION IN BANYUMAS REGENCY - Sheruni Imellia Pamungkas Putri; Swahesti Puspita Rahayu; Nofiyati Nofiyati (Informatika, Universitas Jenderal Soedirman, 2023)
This research derived from inventory management and distribution of the COVID-19 vaccine which is still done manually at the Banyumas Regency Department of Health. The big amount of data that needed to be processed made it difficult for officers to organize the data, as a result there are several problems such as missing and damaged data. This system could make health facilities registered under the Banyumas Regency Department of Health to see the stock items and request the goods faster and easier. The built system has made data management more efficient and effective. Web-based Information System Design of Inventory And COVID-19 Vaccine Distribution In Banyumas Regency uses a waterfall model and qualitative methods. The waterfall model is used to facilitate the creation of this system because it has clear and sequential stages, the qualitative methods used in this study include observation, interviews, and literature studies. The system used PHP and HTML as the programming languages which are then supported by MySQL as the database. The tests carried out to test the system are Black Box Testing and Mean Opinion Score Testing. This research produces a system that can carry out the process of managing and processing inventory data and distribution, the test results show that the system runs as expected and succeeds in facilitating user work to be faster, more effective, and efficient.